Public vs. Private Hospitals in Yemen: Job Satisfaction Differences Among Nurses and Pharmacists - Almualm, Yahya Khamis Ahmed (مجـلـة جـامـعـة السـعيد للعلـوم التطبيقية, 2025)
Back ground and objectives: The Nursing and Pharmacy profession complement each other as well as Nursing work requires effort, hardship, dedication and the same pharmacy, so we discussed the job satisfaction of these two professions. Aim of this Study: To assess the opinion of the Nurses and the Pharmacists about their Satisfaction with the job in (GH), (PH) and compare between them for the purpose of developing institutional work in Hospitals. Method: This study was conducted on the practitioners of Nursing and Pharmacy in each of the Hospitals in the city of Al-Mukalla such as Ibnsina, Universal Hospital, Hospital of Mukalla for Motherhood and Childhood and Private such as hadramout Hospital, al rayan Hospital and Al bourg Hospitals. The method of selection of the study was random as the data were collected by a questionnaire that was filled by the (N, P) and pharmacists themselves. The data were analyzed and the results were extracted. Result: Of the 315 (N, P), 216 were Nurses and Pharmacists from Governmental Hospitals and 99 from private hospitals. The results showed that the Gene ral Satisfaction of (N, P) was higher in Private Hospitals than in Governmental Hospitals at the value (79.8) of mean score. The results showed that there were statistically significant differences between (GH) and (PH) In the satisfaction of (N, P) at the value of (P=0.00). Conclusion: Nurses and Pharmacists in (PH) were more Satisfied than those who were in (GH). Recommendation: The need to develop a comprehensive study including a large sample in order to improve job Satisfaction in (GH) and (PH).